Bibliography of Ethiopian Semitic, Cushitic, and Omotic Linguistics XXV: 2021 - Bulakh, Maria; Krżyzanowska, Magdalena; Panini, Francesca (Aethiopica, 2022)
Bibliography of Ethiopian Semitic, Cushitic, and Omotic Linguistics XXV: 2021